Role of the catalyst structure-activity relationship in enhancing the selective oxidation yield of n-butane to maleic anhydride - Faizan M.; Aamir E.; Kiong T.S.; Song H. (Royal Society of Chemistry, 2025)
Vanadium phosphorus oxide (VPO) catalysts are synthesized for utilization of lighter alkanes such as n-butane to produce maleic anhydride (MA) by a selective oxidation process. Such a process has received huge global attention because of greater selectivity, eco-friendliness and being a less-expensive process as compared to the benzene oxidation process for the production of MA. Herein, we introduced for the first time 2-D MXene Ti3C2 (Mx) into VPO synthesis and prepared Ti3C2@VPO (MXene@VPO; Mx@VPO) nanocomposites via solvothermal and ball milling processes as a promoter and supporter at different (1-5) wt% for the evolution of n-butane selective oxidation. Among them, the solvothermal based promoted catalyst (5% Mx@VPO) exhibited large MA selectivity (up to 11%) as compared to the unpromoted catalyst. Simultaneously, it will decrease the COx selectivity (CO2 and CO). More importantly, the CO : CO2 ratio is reduced up to 1.5 from 2.01, which is beneficial for the environment and chemical plants. From various characterization techniques such as BET, XPS, SEM, TEM, XRD, FT-IR, NH3-TPD, H2-TPR, EDS, EPR, Raman, and TG/DTA we confirmed the role of MXene as a structure directing agent and electron promoting agent in VPO catalysis. ? 2024 The Royal Society of Chemistry.